IMPLEMENTATION OF ALTERNATIVE FORMS OF EDUCATION IN THE TRAINING OF PHYSICAL EDUCATION AND SPORT SPECIALISTS - Fetescu Sava (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
Today, the spectacular evolution in all the fields of social life demands a high-quality training of the human resource, which carries on various types of ever more specialized activities. In order to face both this challenge and the unprecedented dynamic within the training of specialized labour force, the education system has been seeking to adjust, to improve, and to diversify its professional training offer. Considering that the traditional education system is overwhelmed by the current demands, alternative forms of education have been sought, such as distance learning and part-time learning. Despite all scepticism and criticism expressed by some, the alternative forms of education have had a continuous and ascending evolution. Hence, various countries have constituted institutions with exclusive distance learning or of a mixed or dual type, based on an appropriate legal frame and on an analysis of the arguments and opportunities regarding the constitution of such an institution. The implementation of alternative forms of education in traditional university physical education has already gone through several stages. My research sought to elaborate an instruction curriculum model, adapted to the specific of teaching activities through alternative forms of education, but also to the particularities of the specialization and of the students who attend this type of bachelor's studies. Following this endeavour, my purpose was to demonstrate that students who follow the adapted instruction program through alternative forms of education obtain - at the final evaluations - similar values with those of full-time students within the same specialization. After a year - the duration of our experiment -, the two groups of students (full-time students and distance students) obtained very similar results, and the differences were insignificant.